Answer:
![\bold{B)\ (x-2)/(x+1)}](https://img.qammunity.org/2020/formulas/mathematics/high-school/k6nulhmckoq4qgvxga4gf6j9ol2ntlxud6.png)
Explanation:
Factor the numerator (top of fraction) and denominator (bottom of fraction). Then cancel out the common factor.
To factor, find two numbers whose product is the c-value and sum is the b-value.
x² + 5x - 14
∧
-1 +14 = 13
-2 +7 = 5 this works!
So, x² + 5x - 14 = (x - 2)(x + 7)
x² + 8x + 7
∧
1 +7 = 8 this work!
So, x² + 8x + 7 = (x + 1)(x + 7)
![(x^2+5x-14)/(x^2+8x+7)=((x+7)(x-2))/((x+7)(x+1))=(x-2)/(x+1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/1w1gjbpchlnhx0y4yl2ci9jv02j1y3rheo.png)